2013
DOI: 10.2478/s11534-013-0293-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in data communication in wireless sensor networks

Abstract: Abstract:Wireless sensor networks are an important technology for making distributed autonomous measures in hostile or inaccessible environments. Among the challenges they pose, the way data travel among them is a relevant issue since their structure is quite dynamic. The operational topology of such devices can often be described by complex networks. In this work, we assess the variation of measures commonly employed in the complex networks literature applied to wireless sensor networks. Four data communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…(2010) and Cabral et al. (2013). Large synthetic instances based on Binomial Tree (42 instances): Given that the optimal solution for large MBT instances is often unknown, we generated a new benchmark with known optimal solutions using the following procedure.…”
Section: Computational Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…(2010) and Cabral et al. (2013). Large synthetic instances based on Binomial Tree (42 instances): Given that the optimal solution for large MBT instances is often unknown, we generated a new benchmark with known optimal solutions using the following procedure.…”
Section: Computational Resultsmentioning
confidence: 94%
“…We have chosen the small-world model because it is commonly used to represent communication networks in industrial scenarios, as suggested in Guidoni et al (2010) and Cabral et al (2013).…”
Section: Instancesmentioning
confidence: 99%